Comparative evaluation of clinical attachment and alveolar bone levels in patients with infrabony pockets treated by conventional and microsurgical approach – a randomized clinical trial - Raj, Subash Chandra; Tabassum, Shaheda; Mohanty, Devapratim; Katti, Neelima; Baral, Debajani; Sil, Swoyangprava (International Journal of Health Sciences, 2024)
Objectives: The aim of the present study is to evaluate and compare healing outcomes, probing pocket depth reduction, clinical attachment and alveolar bone level following Modified Widman Flap (MWF) with and without 4x prismatic loupe in infrabony pockets. Methods: Patients having at least one infrabony pocket with Probing pocket depth (PPD) ≥5 mm, Angular bone loss ≥3 mm bilaterally were randomly assigned to microsurgical (test) group with MWF using 4x magnifying loupes and conventional (control) group by MWF only. At baseline, 3 and 6 months plaque index, bleeding index, PPD, relative clinical attachment level were taken. Healing outcome was evaluated with healing index by Landry. Pain Score was assessed with Visual Analogue Scale. Percentage of defect depth reduction was assessed by Cone Beam Computed Tomography & Periapical Radiograph. Continuous data between groups was analyzed using unpaired ‘t’ test. Within group comparison was done using Repeated Measures ANOVA followed by multiple pairwise comparison and paired ‘t’ test. Results: There was statistically significant (P = 0.004) reduction in intrabony defect depth in each group evaluated through CBCT. The mean VAS scores after one week of surgical procedure was 3.67 at conventional site compared to 2.9 at microsurgical site which was statistically significant (P = 0.004). Statistically significant (P ≤0.05) healing scores observed for microsurgery group (84.6% after 1 week) compared to control group (15.4% after 1 week). Conclusion: Though blinding of patients and surgeon was difficult and healing indices used are subjective, it can be concluded that microsurgery under 4x magnifying loupe is as effective as conventional MWF in treatment of infrabony pockets but clinical parameters are greatly enhanced by microsurgery with improved healing and less patient discomfort.